2021
DOI: 10.33772/jumbo.v4i3.16680
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Yang Dimediasi Oleh Kepuasan Kerja (Studi Pada Rsud Kabupaten Konawe Kepulauan

Abstract: The purpose of this study is to explain the influence of the Work Environment and Organizational Culture on Employee Performance Mediated by Job Satisfaction. The research approach used was a survey method, data collection was carried out using an instrument in the form of a questionnaire. The study population was all 60 people of the Konawe Kepulauan District Hospital, because the population was relatively small, all of the population became respondents. The analytical tool used in testing the hypothesis is P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The findings of this study are reinforced by Megantara et al (2019) in their research, which revealed that Rotation implemented by leaders influences employee motivation, which in turn affects their work performance. Andriansyah et al (2022) in their study state that work rotation provided to employees affects the motivation felt by all employees undergoing Rotation.…”
Section: The Influence Of Rotation Toward Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study are reinforced by Megantara et al (2019) in their research, which revealed that Rotation implemented by leaders influences employee motivation, which in turn affects their work performance. Andriansyah et al (2022) in their study state that work rotation provided to employees affects the motivation felt by all employees undergoing Rotation.…”
Section: The Influence Of Rotation Toward Motivationmentioning
confidence: 99%
“…Research conducted by Megantara et al (2019) suggests that rotation carried out by leaders will influence employee motivation, affecting their work performance. In their research, Andriansyah et al (2022) state that rotation provided to employees has a positive impact on the perceived motivation of all transferred employees.…”
Section: The Connection Of Rotation Toward Motivationmentioning
confidence: 99%
“…Lingkungan kerja juga menjadi faktor pendukung agar suasan kerja menjadi kondusif ditengah tekanan yang ada, sehingga banyak perusahaan memberikan fasilitas yang bisa digunakan sebagai salah satu faktor untuk melepas penat sementara diareaperusahaan, namun terkadang masalah bukan datang berasal dari luar namun dari dalam diri yang merasa tertekan dan jenuh dengan rutinitas yang tertekan secara terus menerus sehingga mengakibatkan kinerja yang hasilkan menjadi kurang maksimal (Farih et al, 2021).…”
Section: Baik Psikis Ataupun Fisik Setiap Karyawan Harus Benar Benar ...unclassified